COVID-19 and Lassa fever in Nigeria: A deadly alliance?. (April 2022) - Musa, Salihu Sabiu; Zhao, Shi; Abdullahi, Zainab Umar; Habib, Abdulrazaq Garba; He, Daihai
Highlights: The alliance of COVID-19 and Lassa fever has lingering public health concerns. We investigated the synergistic impact of COVID-19 on Lassa fever in Nigeria. We explored possible reasons for decreased Lassa fever cases during the pandemic. We observed potential underreporting of Lassa fever cases owing to SARS-CoV-2. Abstract: As the COVID-19 pandemic poses serious threats to global public health, Nigeria faces a potential public health crisis owing to COVID-19 and other infectious diseases, such as Lassa fever (LF) and malaria. In this study, we discuss the possible determinants behind the decreased number of LF cases in Nigeria, which was likely due to the synergistic impact of the COVID-19 pandemic. During the COVID-19 pandemic, the epidemic curve of LF seems to have deviated from the general seasonal scale seen in past years, which could be due to underreporting of cases. In addition, partial compliance with nonpharmaceutical interventions, limited resources, or human behavior could be contributing factors. Thus, we suggest that better differentiation in terms of human and resource allocation between COVID-19 and LF could help curtail the transmission effectively.